2022
DOI: 10.1109/tits.2021.3061085
|View full text |Cite
|
Sign up to set email alerts
|

Prototyping and Evaluation of Infrastructure-Assisted Transition of Control for Cooperative Automated Vehicles

Abstract: Automated driving is now possible in diverse road and traffic conditions. However, there are still situations that automated vehicles cannot handle safely and efficiently. In this case, a Transition of Control (ToC) is necessary so that the driver takes control of the driving. Executing a ToC requires the driver to get full situation awareness of the driving environment. If the driver fails to get back the control in a limited time, a Minimum Risk Maneuver (MRM) is executed to bring the vehicle into a safe sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Coll-Perales et al [14] address the problem of multiple vehicles engaging in MRM at the same time within the same area due to a failure of transfer of control (ToC). The authors investigate the impact on traffic safety and efficiency of MRM execution when triggered by decentralised environmental notification message (DENM) based or manoeuvre coordination message (MCM) based ToC management schemes.…”
Section: B Cooperative and Collaborative Vehicle Domainmentioning
confidence: 99%
“…Coll-Perales et al [14] address the problem of multiple vehicles engaging in MRM at the same time within the same area due to a failure of transfer of control (ToC). The authors investigate the impact on traffic safety and efficiency of MRM execution when triggered by decentralised environmental notification message (DENM) based or manoeuvre coordination message (MCM) based ToC management schemes.…”
Section: B Cooperative and Collaborative Vehicle Domainmentioning
confidence: 99%
“…2 could be at least postponed to a higher demand, or, in the best case, be avoided at all by AV specific ToR scheduling. Subsequently, the management of downward ToCs and guidance of MRMs to safe spots has been explored via real-world testing by [32]. Their results suggested that the provision of personalized advice to CAVs including information about recommended ToC and safe spot locations could minimize MRMs taking place in lane which can result in hazardous situations.…”
Section: Related Work a Transitions Of Controlmentioning
confidence: 99%
“…To guarantee safety in emergencies, a minimum risk maneuver (MRM) mode is implemented in self-driving systems [13], [14]. In the self-driving industry, the risk avoidance state in the event of a deadline miss is called a minimum risk condition (MRC), and the steering wheel operation and brake control until the vehicle moves to MRC is called MRM.…”
Section: Introductionmentioning
confidence: 99%